Feminist and anticaste pedagogies: A sharmila rege reader - Geetha V.; Chakravarti, Uma (London Routledge, 2024)
This book comprises the collected essays of Sharmila Rege (1964 - 2013), which span a range of themes, including critical perspectives on women's movements, Dalit standpoint feminism, and the relationship between Women's Studies and other disciplines. Written over two decades and more (from the 1990s to 2010), these pioneering essays draw from the struggles and writings of Dalit women, the long history of Anticaste thought in Maharashtra and global feminist debates. Equally, they address enduring concerns to do with caste and gender, and call attention to the inseparability of struggles against caste and patriarchy.
Keywords: Women's studies India; Feminism India; Dalit women India